1971
DOI: 10.2307/1934153
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Territoriality in a Pomacentrid Reef Fish, Pomacentrus Flavicauda Whitley

Abstract: Field observations on territorial behavior of the fish P. flavicauda were made for a total of 200 hours at Heron Island, Great Barrier Reef. Specimens 6 cm or more in length restricted their movements to areas of approximately 2 m over at least a 5-month period. Distribution of the fish was highly correlated (r = 0.89) with the amount of interface between sand and dead coral. Such areas provided algae in close proximity to shelter. Observations of agonistic behavior showed that P. flavicauda usually responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(79 citation statements)
references
References 12 publications
5
73
0
1
Order By: Relevance
“…Format and localities over the 8 sampling occasions. Format and abbreviaabbreviations for each species as Table 5 tions as Increasing ns Omnivore/facultative corallivore ( l ) , (2) gation has also been described with some territorial The more numerous chaetodonts at One Tree Reef species excluding from their territories, fish that utilize exhibited a less obvious form of habitat discrimination, similar resources (Low 1971, Belk 1975 i.e. not by their presence/absence but by their relative Gaines 1986).…”
Section: Spatial Patternsmentioning
confidence: 99%
“…Format and localities over the 8 sampling occasions. Format and abbreviaabbreviations for each species as Table 5 tions as Increasing ns Omnivore/facultative corallivore ( l ) , (2) gation has also been described with some territorial The more numerous chaetodonts at One Tree Reef species excluding from their territories, fish that utilize exhibited a less obvious form of habitat discrimination, similar resources (Low 1971, Belk 1975 i.e. not by their presence/absence but by their relative Gaines 1986).…”
Section: Spatial Patternsmentioning
confidence: 99%
“…In fact, hiding places and high-quality food seem to be common prerequisites for all small territorial herbivores (e.g. Low 1971, Ebersole 1977, Labelle and Nursall 1992, Letourneur 1992, Haley and Müller 2002, Medeiros et al 2010b, given the disadvantageous net costs of defending low-quality territories (see reviews by Dill 1978 andEbersole 1980). Randall (1996) reported that turf algae were the only preferred benthic item of O. trinitatis and filamentous algae were the primary food item of O. atlanticus.…”
Section: Relationship Between Fish Density and Habitat Featuresmentioning
confidence: 99%
“…In the author's opinion, problems on complicated relations between territory and individual space seem to occur not only to the fishes that can shift their territory (Apogon notatus) or overrun their territorial boundary in pursuing intruders, such as Eupomacentrus planifrons (Myrberg et al, 1974), Plecoglossus altivelis (Mizuno et al, 1957) and Gerres oyena (in the spring season of 1976, unpublished data), but also to the fishes showing well defined territories such as Hypsypops rubicunda (Clarke, 1971), Gerres oyena (Usuki, 1976) and Pomacentrus jlavicauda (Low, 1971). Leyhausen (1971) suggested that in sedentary animals, the intolerance toward others expressed as individual distance may increase during the breeding season to the point that it becomes a territory.…”
Section: Spacing-out Behaviourmentioning
confidence: 99%